The ethical approach to AIDS: a bibliographical review - Manuel, C. (Journal of medical ethics, 1990)
This bibliographical study involved first the exploitation of four data-banks: Medline, CNRS, Bioethics and AIDS, with the following key words (in conjunction with AIDS): ethics, human rights, confidentiality, legislation, jurisprudence. A total of 412 references were listed between 1983 and the end of 1987. Examination of the quantitative increase of articles over these years shows that, while references to AIDS and/or HIV infection--referred to as 'AIDS' for brevity--increased by about one third per year, the number of papers treating ethical problems linked to AIDS doubled each year. This increase makes it clear that these problems are important and pressing, that they are evolving rapidly and can be given no easy solution. After reading and analysis of accessible articles in readily comprehensible languages, the different themes can be classified in two categories: 1: Measures intended to protect society (starting with the most coercive); quarantine and isolation; discriminatory measures concerning specific groups; non-respect of the confidential nature of medical information; application of the penal code; screening; obligatory declaration and registration; testing of blood given by donors; vaccination and medical innovations, therapeutic assays; information, education. 2. Measures intended to protect the individual: fundamental rights of the patient: his/her right to confidentiality, to information and to treatment; civil rights: civil liberty, right to education, right to work, etc...; rights of the healthy individual: right of those in contact with the patients, safety of hospital staff, of those receiving blood-transfusions, etc... The legislation adopted in the various countries and the main opinions to be found in these articles are listed and analysed, and for each particular theme it is possible to refer to a list of the 232 most important articles. While the debate seems to concentrate on the conflict between the right of society to protect itself against the spread of infection and the 'civil' rights of the infected minorities, our conclusion tends to reduce this antagonism, showing that, particularly as far as the confidential nature of medical information is concerned, measures intended to protect the individual also protect society.